Coastal mites (Oribatida, Ameronothridae) found far from the coast in moss growing on the Cathédrale Notre-Dame de Paris, France, fifty years after their first discovery in this historic site - Shimano, Satoshi; Hiruta, Shimpei F.; Sánchez-Chávez, Daniel Isaac; Pfingstl, Tobias (Zootaxa, 2024)
A species of oribatid mite, Ameronothrus maculatus (Michael, 1882), was collected from moss growing on the building of the Cathédrale Notre-Dame de Paris. This species of Ameronothridae is usually found in coastal Holarctic environments. The specimens were studied by Scanning Electron Microscope and could be clearly assigned to this taxon. This population was first discovered by F. Grandjean approximately 50 years ago, and the present record demonstrates that it has persisted despite its habitat being a tourist destination visited by over 14 million people annually. The record of this species far upstream and on anthropogenic structures is rare but not out of the ordinary in Northern Europe where its distribution can reach far beyond the edges of the estuaries. For further confirmation, we obtained DNA sequences for the COI gene (1554 bp, LC848687), and they were almost identical to those of an earlier found and sequenced specimen of A. maculatus from Germany, differing by only a single base. As supplemental information on A. maculatus from Paris, the region includes whole nucleic ribosomal RNA genes (18S, 5.8S, and 28S, LC848688), partial elongation factor 1 alpha (LC848689), and the complete nucleotide sequence of mitochondrion were also determined.